Discontinuous space variant sub-wavelength structures for generating radially polarized light in visible region - Ghadyani, Zahra; Rothau, Sergej; Lindlein, Norbert; Leuchs, Gerd; Lohse, Olga; Harder, Irina (Journal of the European Optical Society: Rapid Publications, 2011)

Optimised exposure strategies for artifial waveplates - Harder, Irina; Lohse, Olga; Rothau, Sergej; Piaszenski, Guido (39th International Conference on Micro and Nano Engineering, 2013)

Silicon dual pillar structure with a distributed Bragg reflector for dielectric laser accelerators: Design and fabrication - Yousefi, Peyman; McNeur, Joshua; Kozak, Martin; Niedermayer, Uwe; Gannott, Florentina; Lohse, Olga; Boine-Frankenheim, Oliver; Hommelhoff, Peter (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
Dielectric laser accelerators (DLAs) have proven to be good candidates for miniaturized particle accelerators. They rely on micro-fabricated dielectrics which are able to modulate the kinetic energy of the incoming electron beam under a proper laser illumination. In this paper we demonstrate a dual pillar structure with a distributed Bragg reflector to mimic a double sided illumination to the electron path. The structure is fabricated by an electron beam lithography technique followed by a cryogenic reactive ion etching process. Such a structure can accelerate the injected 28 keV electrons by a gradient of approximately 150 MeV/m which can be further optimized towards the GeV/m regim
Keywords: Dielectric laser accelerators; Dual pillar structure; Distributed Bragg reflector; Electron beam lithography; Cryogenic reactive ion etching

Strukturierungsfehler diffraktiv optischer Elemente - Berger, Andreas; Harder, Irina; Lohse, Olga; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)